2021
DOI: 10.1002/app.52003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an oxyalkylated lignin‐g‐polylactic acid copolymer to improve the compatibility of an organosolv lignin in blended poly(lactic acid) films

Abstract: To improve the compatibility of an organosolv lignin (OL) in polylactic acid (PLA) blends, a green approach was pursued whereby the lignin was modified with propylene carbonate (PC) to increase its aliphatic hydroxyl content, and thereby, its reactivity. The oxyalkylated organosolv lignin (OOL, synthesized at 170°C) was analyzed by quantitative 31P NMR and showed the number of phenolic hydroxyls decreased from 4.73 to 0.16 mmol·g−1, and the number of aliphatic hydroxyls increased from 3.56 to 3.92 mmol·g−1. OO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Comparison of UV blocking % and transmittance % of our best samples with previously reported lignin-based materials. [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of UV blocking % and transmittance % of our best samples with previously reported lignin-based materials. [1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16] …”
Section: Resultsmentioning
confidence: 99%
“…18 For this reason, organosolv lignin is under study for the preparation of added-value materials such as aerogels, 38 coating materials, 39,40 tissue engineering, 41 nanoparticles, 42-44 adhesives, [45][46][47] bio-composites for 3D-printing, [48][49][50] recyclable and self-healing polymers, 51,52 antioxidant agents, [53][54][55] UV-absorber agents, 56 metal absorbers for wastewater treatment, 57,58 stabilisers of cellulose nitrate, 59 flame retardant resins, 60 polyurethane foams, 61 antimicrobial agents 62,63 and bio-films. 64…”
Section: Ligninmentioning
confidence: 99%
“…The prepared blend film showed impressive UV-absorption ability and could be used as a well-dispersed UV biocompatible packaging material. 122 Furthermore, to explore their potential applications, PLA films were prepared with the incorporation of different contents of lignin nanoparticles using the extrusion method. The results showed that lignin nanoparticles endowed PLA films with UV resistance, anti-oxidation, and antibacterial properties, especially when the lignin content was higher.…”
Section: Biodegradable Substratesmentioning
confidence: 99%